Update on otitis media – prevention and treatment - Qureishi, Ali; Lee, Yan; Belfield, Katherine; Birchall, John P.; Daniel, Matija (Dove Medical Press, 2014)
Acute otitis media and otitis media with effusion are common childhood disorders, a source of significant morbidity, and a leading cause of antibiotic prescription in primary health care. Although effective treatments are available, some shortcomings remain, and thus better treatments would be welcome. Recent discoveries within the field of otitis media research relating to its etiology and pathogenesis have led to further investigation aimed at developing novel treatments. This article provides a review of the latest evidence relating to the understanding of acute otitis media and otitis media with effusion, current treatment strategies, their limitations, new areas of research, and novel strategies for treatment.